2015
DOI: 10.1039/c5tc01531f
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) in the visible region

Abstract: We report a broad photoluminescence (PL) band of poly (3,4ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT/PSS) ranging from 1.2 to 3.0 eV over the full range of the visible region. Comparison with the PL of related materials reveals that the origin of the observed PL of PEDOT/PSS is PSS. This study indicates that the removal of excess PSS improves the optical properties of PEDOT/PSS for application as transparent electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The broadband emission can be attributed to the formation of the excimer due to aromatic group interaction. The broadband visible luminescence with the maximum at 2.3 eV was reported recently by Kayoma, [ 27 ] and was attributed to PSS. The blueshift of the maximum energy in our samples can be explained by the strong dependence of the emission from PSS on the excitation wavelength.…”
Section: Resultssupporting
confidence: 60%
“…The broadband emission can be attributed to the formation of the excimer due to aromatic group interaction. The broadband visible luminescence with the maximum at 2.3 eV was reported recently by Kayoma, [ 27 ] and was attributed to PSS. The blueshift of the maximum energy in our samples can be explained by the strong dependence of the emission from PSS on the excitation wavelength.…”
Section: Resultssupporting
confidence: 60%
“…A spectral response function was obtained using a tungsten standard lamp. Because this measurement system can detect weak Raman scattering signals in doped polythiophenes, PL signals, if weak, are also measurable …”
Section: Methodsmentioning
confidence: 99%
“…Photoluminescence from PEDOT:PSS has not been extensively investigated so far, hence controversy still remains regarding the identification of the PL emission. Koyama et al [32] attributed PSS to be responsible for PL emission from 1.2 to 3 eV. Some other authors [21] proposed emissions around 3 eV are due to PSS chains.…”
Section: Pedot:pss Polymermentioning
confidence: 99%
“…Some authors reported that, when the surface of the nanoparticles embedded in the polymer is positively charged, the negatively charged PSS chains can be electrostatically attracted, leading to changes in the PEDOT:PSS chains' configuration, which can enhance the electrical conductivity [21]. Rearrangement of the PEDOT:PSS can lead to better pathways for charge transport-actually, an expanded-coil configuration is usually associated with improved conductivity [32]. Hence, in this case, synergy between the counterparts in the composite leads to improved electrical performance.…”
Section: Hybrid Composite (Sno and Pedot:pss)mentioning
confidence: 99%